CARBOCYSTEINE LYSINE SALT MONOHYDRATE IN TREATMENT OF DISEASES OF LOWER RESPIRATORY TRACT IN CHILDREN - T. A. Kruchkova (Вопросы современной педиатрии)
Inflammatory diseases of the respiratory tract are characterized by changes in rheological properties of the phlegm and lower of the mucociliary clearance. Adjustment of mucoregulatory agents is of a special significance in treatment of diseases of the lower respiratory tract in children. Aim: to assess efficacy of carbocysteine lysine salt monohydrate as a mucokinetic agent in children with respiratory tract diseases. Patients and methods: 65 children (31 girls and 34 boys) aged from 5 to 16 years old with acute respiratory tract diseases received treatment in Belgorod pediatric out-patient clinic № 4 were included into the study. The results of the clinical follow-up of these children are shown in the article. Results: carbocysteine lysine salt monohydrate was found to be effective and safe in treatment of acute and chronic inflammatory diseases of the respiratory tract in children. The authors observed quicker convalescence of the patients and possibility of combination of this drug with other medicines used in pediatric practice. Conclusions: the above-mentioned drug when used in combination with antibacterial agents intensifies penetration of the latter into the bronchial secretion and bronchial mucous membrane thereby increasing their efficacy. The drug does not have toxicity, is well-tolerated even when prolonged using and can be recommended for treatment of cough in children both under out- and in-patients conditions.Keywords: children, respiratory tract diseases, carbocysteine.